KAMPUNG-KOTA DAN PERMUKIMAN KUMUH DI KOTA BANDUNG TAHUN 1965-1985 Bagas Yusuf Kausan - Kausan, Bagas Kausan (Badan Pengembang Konservasi UNNES, 2019)
In the 1970s-1980s, along with the development planning of the metropolitan city, the issue of the settlements into a single symptom that happens almost in every big city in Indonesia. This is caused by the limited capacity of the city, while a surge in population resulting from urbanization continued to increase. As a result many migrants who later settled in land unused and filling the pockets of the kampung-kota of the city which had previously existed. This study discusses the history of the kampung-kota, especially those associated its position in an increasingly modern city planning. Further, this research is trying to see how the Government viewed the kampung-kota and simultaneously reviewed what efforts the Government has to improve the environment of the settlement. After observation, in the 1970-1980s, various forms of the settlement repair program ever undertaken in the city of Bandung. Although there is also a pure settlement improvement program was initiated by the non-governmental community, in the majority of program improvements the kampung-kota at that time was a Government project that worked with philanthropic foundations. But just take a focus on improvements to the physical aspect of the kampung-kota, a few repair program was not significantly impact on the community which settled in the settlement of the city. For improving the environment of settlement does not warrant improving the condition of their economy are more absorbed into the urban informal economy.